AKTIVITAS ANTIOKSIDAN DARI DAUN LALAPAN (THE ANTIOXIDANT ACTIVITY OF LALAPAN LEAFS) - Fatimah, Feti (Jurnal Entropi, 2006)
This Research was to determined of the total of phenol content and also to test the antioxidant activity of four lalapan leafs that are kemangi (sweet bacil, Ocinum Bacilicum), kemang (Mangifera kemanga), selada (cress) and also poh pohan (Pilea trinervina). The total of phenol content of extract of lalapan leafs determined as tannic acid, whereas the test of antioxidant activity determined by method of diene conjugation. The result of analysis indicated that the total of the highest phenol content is extract of kemang leaf (1,14 mg/g), followed by pohpohan (0,84 mg/g), kemangi (0,68 mg/g) and also selada (0,54 mg/g). Pursuant to concentration of diene conjugation, knew that the kemang has the highest activity than the other lalapan leafs.